Analisis Kekerasan Pada Roda Gigi Hasil Pengerasan Menggunakan Pemanas Induksi - Faisal, Reza Arfi; Ariyanto, Nur Aidi; Faoji, Ahmad; Akhmadi, Amin Nur (Rekayasa Material, Manufaktur dan Energi, 2020)
Vehicles with engine characteristics that are capable of producing large torque to accelerate the vehicle. The gear is one of the vehicle engine components in the transmission system which functions to transmition power from the drive shaft to the shaft to be driven. For gear hardening, many IKM have limited capabilities. One of the hardening tools that can be used by IKM is an induction heating device. The purpose of this study was to analyze the hardness of the AISI P20 material gears after induction hardening of the gear specimens before and after treatment by taking induction hardening test data using variations of the output current, namely 820A and 1100A and coils 2 and 3 turns. The results of this study obtained the highest hardness testing parameters, namely in the gear specimen 4 using 3 coils, the measured frequency was 29 kHz, the maximum position output current was 1100A. heating time for 32 seconds, the cooling medium is quench oil and the maximum hardness value is 1561 HV.